Bronchogenic Cyst in the Head and Neck Region. Issue 4 (June 2017) - Lee, Dong Hoon; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract : Objective: The objective of this study was to review the clinical characteristics and surgical treatment outcomes of patients with bronchogenic cysts in the head and neck region. Methods: A retrospective chart review was performed at Chonnam National University Hwasun Hospital from January 2006 to May 2016. Results: Eight patients with a final diagnosis of bronchogenic cyst in the head and neck region were identified based on their medical records. The most common location for the head and neck lymphatic malformations was the neck (4 patients), followed by the soft palate (1 patient), the posterior pharyngeal wall (1 patient), the floor of mouth (1 patient), and the arytenoid (1 patient). The size of the lymphatic malformations ranged from 1 to 6 cm. Bronchogenic cysts recurred in 2 patients. Both these patients were disease-free after the revision operation. No major complications resulting from the surgical intervention were observed. Conclusion: Bronchogenic cysts are rare congenital malformations and they can occur at various sites in the head and neck region. Bronchogenic cyst should be considered in the differential diagnosis of midline and lateral neck masses or intraoral cysts.